If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24x + -2y = 3 Solving 24x + -2y = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. 24x + -2y + 2y = 3 + 2y Combine like terms: -2y + 2y = 0 24x + 0 = 3 + 2y 24x = 3 + 2y Divide each side by '24'. x = 0.125 + 0.08333333333y Simplifying x = 0.125 + 0.08333333333y
| -4m-6=-3 | | 4t-6=-4 | | 8z+16=31 | | 11x+4=76 | | 19n-14=50 | | -2x^2+4x+16=x-4 | | 19p+10=138 | | 12p+9=90 | | 1=314.019418x+24673.20799626468y | | 9m-14=-2 | | ydx-(x^2-1)*dy=0 | | 9x-11=37 | | (6+2)x(12-9)= | | X-8y=-105 | | (8+2)x(12-9)= | | 8x-1=5x-10 | | 4y^4-4y^3+6y^2+3y+2.25=0 | | 8y-8y=-105 | | 7x-15=25 | | 0=2*x | | 20x+11=130 | | 8n-10=35 | | 2(2k-1)=28 | | 5z+16=31 | | x/(x^2)=4 | | 16n-14=50 | | 16p+10=138 | | 9p+9=90 | | 7x+13y=9 | | 6m-14=-2 | | (2s-1)(2)=25 | | x+0.5x=50 |